1993
DOI: 10.1139/f93-218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Population Characteristics of Muskellunge (Esox masquinongy), Northern Pike (E. lucius), and Their Hybrid (E. masquinongy × E. lucius)

Abstract: We compared growth, survival, diet, and angler catch of muskellunge (Esox masquinongy), northern pike (E. lucius), and tiger muskellunge (E. masquinongy × E. lucius) through 5 yr after their introduction into three Ohio reservoirs. Muskellunge grew slower than northern pike and tiger muskellunge through the first year but faster than northern pike in subsequent years. Large stocked esocids (180–205 mm) survived better than small ones (145 mm). Survival patterns established through the first fall were maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Northern pike diets were dominated by yellow perch in some previous studies (e.g., Chapman et al 1989), but also by other prey fish species such as walleye (Sammons et al 1994), gizzard shad Dorosoma cepedianum (Lesueur) (Wahl & Stein 1993), common carp Cyprinus carpio (Linnaeus), and black crappie (Sammons et al 1994). Northern pike in Spirit Lake ate yellow perch almost exclusively.…”
Section: Discussionmentioning
confidence: 70%
“…Northern pike diets were dominated by yellow perch in some previous studies (e.g., Chapman et al 1989), but also by other prey fish species such as walleye (Sammons et al 1994), gizzard shad Dorosoma cepedianum (Lesueur) (Wahl & Stein 1993), common carp Cyprinus carpio (Linnaeus), and black crappie (Sammons et al 1994). Northern pike in Spirit Lake ate yellow perch almost exclusively.…”
Section: Discussionmentioning
confidence: 70%
“…The muskellunge has a somewhat more southerly distribution, but there is extensive overlap between the two species. Comparative ecological studies reveal only minor dietary differences, relating to such parameters as preferred prey size (Wahl and Stein 1993). Interestingly, the northern pike is a cosmopolitan species distributed across the Palearctic and Nearctic, whereas the muskellunge is endemic to North America.…”
Section: Discussionmentioning
confidence: 99%
“…But where low persistence rules out possible effects of Shoepack ancestry, MNDNR biologists can focus on other biotic and abiotic factors if size structure is a concern. Studies have shown that muskellunge grow more slowly depending on the species (Wahl and Stein 1988) and size (Wahl and Stein 1993) of available prey. Abiotic factors, especially temperature, have been shown to affect muskellunge growth (Bevelhimer et al 1985;Wahl and Stein 1991;Clapp and Wahl 1996).…”
Section: Management Implicationsmentioning
confidence: 99%